The Effectiveness of Guided Inquiry Learning Model with Edmodo Assisted to Facilitate Critical Thinking Skills - Sejati, Andri Estining; Syarifuddin, Syarifuddin; Nasruddin, Nasruddin; Miftachurohmah, Nisa; Nursalam, La Ode; Hariyanto, Eko (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This research aims to develop a learning device based on a guided inquiry model with Edmodo on the subject of earth structure and disasters which is appropriate to practice critical thinking skills of junior high school students. The research subjects were learning devices and class IX students of SMP Negeri 17 Kendari. This research is a development research using the Dick and Carey model. Testing the results of the development of the device in classroom learning using a one group pretest-posttest design. The data analysis technique used quantitative descriptive and qualitative descriptive. The findings from the results of this research are: The validity of learning tools is in good category, the implementation of lesson plans is in good category; the most dominant student activity during learning is making observations; student response to guided inquiry learning model with Edmodo is considered good; completeness of students' concept understanding learning outcomes, the average pretest was 16.47 and posttest was 87.06. While the students' critical thinking skills learning outcomes, the average pretest was 20.53 and posttest was 85.67. The obstacle encountered during learning is the time required to carry out learning activities beyond the specified time. Based on the discussion of the results and findings, it is concluded that the guided inquiry model learning with Edmodo tool that has been developed on the earth structure and disaster material is appropriate to be used to train the critical thinking skills of junior high school students.